(untitled) (Academicia Globe: Inderscience Research, 2023)
This article describes in detail the importance of using new pedagogical technologies in teaching English, the fact that some teachers do not know how to use and do not use technologies during English classes, and the most effective ways to teach and learn a foreign language using modern technologies.